KAJIAN KONSENTRASI GULA DAN ASAM SITRAT TERHADAP SIFAT KIMIA DAN ORGANOLEPTIK SELAI PISANG NANGKA (MUSA PARADISIACA FORMATYPICA) - Lina Herlinawati; Ida Ningrumsari; Tharisa Anggraeni (Ma'soem University, 2022)
Pisang nangka (Musa paradisiaca formatypica) is a type of banana that is consumed in processed form. One way of processing pisang nangka (Musa paradisiaca formatypica) is making it into pisang nangka jam. This product is in the form of paste which is processed by cooking pisang nangka pulp added with sugar and citric acid. The purpose of this study is to find out the effect of sugar and citric acid concentrations on several characteristics resulted from pisang nangka jam. And the aim is to determine the right sugar and citric acid, so it can produce pisang nangka jam with good characteristics. The experimental design used in this study is randomized block design (RBD) with a factorial pattern, each factor consisting of 5 levels and 3 levels, repeated 3 times. The first factor is sugar concentration (g) consisting of 5 levels, namely: g1 = 57.5%, g2 = 60.0%, g3 = 62.5%, g4 = 65.0%, g5 = 67.5%. The second factor is citric acid concentration (S) which consists of 3 levels, namely: s1 = 0.25%, s2 = 0.30%, s3 = 0.35%. Observation is conducted on sucrose content, water content, pectin content, and organoleptic assessments of aroma, spreadability, taste, color, and overall acceptance.